Bakti Sosial Di SMA Negeri 03 Kota Batam Provinsi Kepulauan Riau - Dailami; Tirta Mulyadi; Haufi Sukmamedian (PUSLITABMAS-Politeknik Pariwisata Batamc, 2023)
Social service or better known as social service is an activity that manifests concern or a sense of humanity towards fellow human beings. Where with this activity we can attach our sense of kinship to other people. The word social includes both individuals and groups. Devotion can be interpreted as binding (binding) oneself to self or other selves. This bond is in the form of caring, a feeling of responsibility for the lives of others. Social service can mean giving something (to those who need a gift).